2002
DOI: 10.1007/s00213-001-0973-2
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning tastant and the acquisition of conditioned taste avoidance to drugs of abuse in DBA/2J mice

Abstract: CTA induced by morphine or cocaine in mice occurs in a similar pattern to that seen in rats, and these findings agree with an interpretation based on drug reward. In contrast, ethanol-induced CTA is more likely attributable to aversive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
(67 reference statements)
0
25
0
Order By: Relevance
“…This procedure was performed according to established protocols (Risinger and Boyce, 2002;Chester et al, 2003). Animals were housed singly and acclimatized to limited water access by allowing them access to water for decreasing periods of time (10,8,6, and 4 hr per day on subsequent days), followed by 2 hr daily access for 1 week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure was performed according to established protocols (Risinger and Boyce, 2002;Chester et al, 2003). Animals were housed singly and acclimatized to limited water access by allowing them access to water for decreasing periods of time (10,8,6, and 4 hr per day on subsequent days), followed by 2 hr daily access for 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…Having established that the rewarding effects of ethanol are altered in Ca v 2.2 null mice, we next investigated the aversive properties of ethanol using a conditioned taste aversion assay with ethanol as the unconditioned stimulus and 1.2% NaCl as the CS. Using 1.2% NaCl as the CS is thought to measure genuine aversion to ethanol, rather than reward, which may be measured using saccharin as the CS (Grigson, 1997;Risinger and Boyce, 2002;Chester et al, 2003). After commencement of ethanol treatment, both genotypes rapidly developed conditioned taste aversion.…”
Section: Conditioned Taste Aversion Is Attenuated In Ca V 22 Null Micementioning
confidence: 99%
“…Aragon et al 1991a;Broadbent et al 2002), the results of the present experiment showed that ethanol induced a strong dose-dependent CTA. The CTA induced by ethanol was shown to be dependent upon the aversive properties of ethanol in both mice (Broadbent et al 2002;Risinger and Boyce 2002) and rats (Froehlich et al 1988). …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that ethanol-induced CTA is mediated by its aversive properties in naive animals (Froehlich et al 1988;Broadbent et al 2002;Risinger and Boyce 2002). Considering the strong reinforcing properties of brain acetaldehyde, it may be suggested that acetaldehyde-induced CTA is mediated by its rewarding properties, although additional studies are required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation